2017
DOI: 10.1002/prot.25253
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial scoring function for protein–RNA docking

Abstract: Protein-RNA docking is still an open question. One of the main challenges is to develop an effective scoring function that can discriminate near-native structures from the incorrect ones. To solve the problem, we have constructed a knowledge-based residue-nucleotide pairwise potential with secondary structure information considered for nonribosomal protein-RNA docking. Here we developed a weighted combined scoring function RpveScore that consists of the pairwise potential and six physics-based energy terms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In fact, RNA rarely acts alone, and most RNAs function only in complex with specific proteins (Dawson and Bujnicki 2016). Therefore, revealing the protein-RNA specific recognitions and binding patterns is quite significant for both understanding the important processes of life and designing new drugs (Zhang et al 2017). Several experimental methods have been developed to determine RPIs (Anko and Neugebauer 2012;Campbell and Wickens 2015), such as ultraviolet crosslinking and immunoprecipitation (CLIP) (Ule et al 2003), high-throughput sequencing of CLIP cDNA library (HITS-CLIP) (Licatalosi et al 2008), photoactivatable-ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) (Hafner et al 2010), individual nucleotide resolution CLIP (iCLIP) (Konig et al 2010), targets of RNA-binding protein identified by editing (TRIBE) (McMahon et al 2016), covalent RNA marks (Lapointe et al 2015), interactome capture (IC) (Castello et al 2012), and serial RNA interactome capture (Ser IC) (Conrad et al 2016), etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, RNA rarely acts alone, and most RNAs function only in complex with specific proteins (Dawson and Bujnicki 2016). Therefore, revealing the protein-RNA specific recognitions and binding patterns is quite significant for both understanding the important processes of life and designing new drugs (Zhang et al 2017). Several experimental methods have been developed to determine RPIs (Anko and Neugebauer 2012;Campbell and Wickens 2015), such as ultraviolet crosslinking and immunoprecipitation (CLIP) (Ule et al 2003), high-throughput sequencing of CLIP cDNA library (HITS-CLIP) (Licatalosi et al 2008), photoactivatable-ribonucleoside-enhanced crosslinking and immunoprecipitation (PAR-CLIP) (Hafner et al 2010), individual nucleotide resolution CLIP (iCLIP) (Konig et al 2010), targets of RNA-binding protein identified by editing (TRIBE) (McMahon et al 2016), covalent RNA marks (Lapointe et al 2015), interactome capture (IC) (Castello et al 2012), and serial RNA interactome capture (Ser IC) (Conrad et al 2016), etc.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two standalone docking software packages, including NPDock (Tuszynska et al 2015) and 3dRPC , have been developed specifically for predicting protein-RNA complexes. Similar to most docking protocols, a protein-RNA docking approach includes two steps: sampling and scoring (Zhang et al 2017). Several approaches have been developed to solve the sampling issue, such as the information-driven method used in HADDOCK (Dominguez et al 2003), the fast Fourier transformation (FFT) algorithm in GRAMM (Vakser and Aflalo 1994) and FTDock (Katchalskikatzir et al 1992), the distance geometry algorithm in DOCK (Kuntz et al 1982), and the genetic algorithm in DARWIN (Taylor and Burnett 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, the aromatic and Arg residues have important contributions to the stacking and ion-pi interactions with RNA bases respectively, which may explain the reason of their higher conservations. Based on our previous study [29,32], the hydrophobic residues Leu, Ile and Met do not prefer to appear at protein-RNA interfaces, while interestingly they prefer to occur in the conserved interface clusters once they appear at interfaces. Considering the analysis results on hot spot residues that the hydrophobic residues have the second largest probability of being hot spot residues among the seven classes of amino acid residues, we think that the three kinds of preferred hydrophobic residues in conserved interface clusters maybe contribute an important role to protein-RNA binding free energy through their cooperative interactions with other residues in the conserved interface clusters.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the analysis results on hot spot residues that the hydrophobic residues have the second largest probability of being hot spot residues among the seven classes of amino acid residues, we think that the three kinds of preferred hydrophobic residues in conserved interface clusters maybe contribute an important role to protein-RNA binding free energy through their cooperative interactions with other residues in the conserved interface clusters. Additionally, the residue-nucleotide propensity potential obtained by us [29,32] for protein-RNA interactions showed that Cys has a higher pairing preference with A and U, and Gly is relatively preferred by interfaces. For protein-RNA, protein-protein (homodimers and heterocomplexes) interactions, the common residues preferred in conserved clusters are Leu, Ile, Met, Tyr, Phe and Trp.…”
Section: Discussionmentioning
confidence: 99%